TELEVISION'S ROLE IN CONTEMPORARY EDUCATION AND THE CURRENT DEMAND FOR EDUCATIONAL CONTENT - Zaynitdinova Munira Fazliddinovna (Ecominds Press, 2025)
The question of how educational shows benefit viewers remains a provard. At this point, a number of questions need to be answered. How successful are these TV shows in satisfying the desires of viewers? Is the purpose of educational TV programs to replenish airtime? Have the issues of demand for educational television shows been explored? So, are the requirements and opportunities for educational demonstrations in such a situation balanced? The role and opportunities of television in education: is the concept of value important in television education? The article answers similar questions.
Keywords: Educational television, television, educational program, educational value, education, thinking, intellectual thinking.